Enriching Learners’ Vocabulary by Means of Derivative Word-Building Patterns - Karapetyan, Lili (Armenian Folia Anglistika, 2007)
The English vocabulary has increased greatly in more than 1500 years of development. It is more extensive than that of any other language in the world. Certain processes have led to the creation of many new words as well as to the establishment of patterns for further expansion. Among these processes are affixation, compounding and conversion, which are the three main types of word-formation characteristic of the English language.Since there are few practical rules of compounding and conversion, it would be reasonable to focus on affixation, derivative word-building patterns in particular. Derivative word-building patterns are likely to develop the learners’ receptive and reproductive skills. With the receptive skills the learners make informed guesses about the meaning of unknown items, thus enriching their potential vocabulary. In terms of reproductive skills knowledge of some productive word-building patterns serve to widen the learners’ creative abilities. This can also be viewed as a communicative strategy.